1.62 Stimulated by IL-15 regulatory T cells CD4+CD25++ (Tregs) isolated form bone marrow of rheumatoid arthritis (RA) patients suppress proliferation but not TNF production by responder CD4+CD25- T cells. (31st January 2014) - Massalska, M; Radzikowska, A; Kuca-Warnawin, E; Plebanczyk, M; Skalska, U; Burakowski, T; Janicka, I; Kornatka, A; Maldyk, P; Kontny, E; Maslinski, W
Abstract : Background: Previous studies from our laboratory have supported the concept that BM can actively participate in the pathogenesis of RA by TLR triggered B cell activation and distinct subpopulations of mature lymphocytes present in BM of osteoarthritis (OA) and RA patients. In the present study we analysed presence and functional activity of CD4 + CD25 ++ Tregs isolated from RA and OA bone marrow samples. Materials and Methods: Bone marrow mononuclear cells (BMMC) were obtained from BM of RA and OA patients undergoing hip bone replacement surgery. The Tregs phenotype and number was assessed by FACS analysis immediately after isolation. After in vitro 72h culture of BMMC with or without IL-15, CD4 + CD25 +++ Tregs were isolated by cell sorter for functional activity measured in proliferation assays and TNF and IL-17 production. Results: As reported previously, CD4 + Foxp3 + regulatory T cells are present in OA BM at higher number than in RA patients (4.7% vs 2.6% of CD4 +, p = 0.0075). Tregs from both OA and RA BM suppress CD4 + CD25 - T cells proliferation (respectively 52.4%; p = 0.0001 in OA and 52.3%; p = 0.0001 in RA). After stimulation of BMMC by IL-15, suppression was similar (48.5%; p = 0.00006 in OA and 47.3%; p = 0.002 in RA). Tregs from OA patients suppress TNF production by CD25 - cells independently on IL-15 stimulation (respectively 26.3%; p = 0.0001 in control and 30.2%; p = 0.0001 after IL-15 stimulation). In contrast to OA, Tregs isolated from RA patients suppress TNF production only in control (30.7%; p = 0.00005) but not after IL-15 stimulation (79.8%; ns). IL-15 does not trigger increase of CD4 + Foxp3 + IL-17 + cell number (respectively 0.5% vs 0.5% in OA and 0.3% vs 0.1% in RA), although stimulates IL-17 production by these cells (8904.8 vs 3525.5; p = 0.008 in OA and 7522.0 vs 3901.8; ns in RA). Conclusions: Partial dependence of (overproduced in RA BM) IL-15 triggered Foxp3 expression, suggests that immunosuppression is an active process that takes part in bone marrow. However, lower number and limited functionality of Tregs present in RA bone marrow in comparison to OA may account for less efficient inhibition of T-cell activation in RA.